2018
DOI: 10.3748/wjg.v24.i34.3884
|View full text |Cite
|
Sign up to set email alerts
|

Formin-like 3 regulates RhoC/FAK pathway and actin assembly to promote cell invasion in colorectal carcinoma

Abstract: AIMTo clarify the underlying mechanism of formin-like 3 (FMNL3) in the promotion of colorectal carcinoma (CRC) cell invasion.METHODSThe in vitro biological function analyses of FMNL3 were performed by gain- and loss-of function approaches. Changes in the F-actin cytoskeleton were detected by the technologies of phalloidin-TRITC labeling and confocal microscopy. The signaling pathway mediated by FMNL3 was explored by western blot, gelatin zymograph assay, co-immunoprecipitation (co-IP), immunofluorescence co-lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Further analysis revealed that increased HOXD10 led to suppression of the MAPK and AKT pathways known to regulate RhoC [68]. The interaction of FMNL-3 with RhoC was seen to lead to increased MMP2, MMP9 and VEGF, consequently leading to increased invasion in colon cancer cell lines [69]. The knockdown of RhoC in cholangiocellular carcinoma cells on the other hand, resulted in the suppression of invasion and migration [70].…”
Section: Introductionmentioning
confidence: 99%
“…Further analysis revealed that increased HOXD10 led to suppression of the MAPK and AKT pathways known to regulate RhoC [68]. The interaction of FMNL-3 with RhoC was seen to lead to increased MMP2, MMP9 and VEGF, consequently leading to increased invasion in colon cancer cell lines [69]. The knockdown of RhoC in cholangiocellular carcinoma cells on the other hand, resulted in the suppression of invasion and migration [70].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, FMNL2 has been regarded as a potential target for abnormal proliferation in colorectal cancer [ 25 , 26 ]. FMNL1 increases the proliferation of leukemia cells [ 27 ], and FMNL3 promotes cell proliferation and clonogenicity in colorectal cancer [ 28 ]. However, the function of FMNL2 in breast cancer cell proliferation has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…C/EBPs are a family of transcription factors including CEBPG that regulate growth and differentiation of various tissues and control redox homeostasis in normal and cancerous cells [ 33 34 ]. FMNL3 is an oncogene in tongue squamous cell carcinoma, nasopharyngeal carcinoma, and colorectal carcinoma [ 35 36 ]. This study found that circFoxp1 positively regulated the expression of CEBPG and FMNL3 through miR-22 and miR-150-3p, suggesting that CEBPG and FMNL3 are oncogenes in ovarian cancer, but the specific regulatory mechanism still needs more experimental proof.…”
Section: Discussionmentioning
confidence: 99%